Cyber Chutzpah: The Sony Hack and the Celebration of Hyperbole. - Berghel, Hal (Computer (00189162), 2015)
There's nothing about the recent Sony hack that withstands close scrutiny. The story began as bunk, took a spin around blather and hooey, and then seems to have come to rest on drivel.